Dairy Fat Consumption and the Risk of Metabolic Syndrome: An Examination of the Saturated Fatty Acids in Dairy - Unger, Allison L. (Nutrients, 2019)
Lifestyle is a key modifiable risk factor involved in the manifestation of metabolic syndrome and, in particular, diet plays a pivotal role in its prevention and development. Current dietary guidelines discourage the consumption of saturated fat and dietary sources rich in saturated fat, such as dairy products, despite data suggesting that full-fat dairy consumption is protective against metabolic syndrome. This narrative review assessed the recent epidemiological and clinical research that examined the consumption of dairy-derived saturated fatty acids (SFA) on metabolic syndrome risk. In addition, this review evaluated studies of individual SFA to gain insight into the potential mechanisms at play with intake of a diet enriched with these dairy-derived fatty acids. This work underscores that SFA are a heterogenous class of fatty acids that can differ considerably in their biological activity within the body depending on their length and specific chemical structure. In summary, previous work on the impact of dairy-derived SFA consumption on disease risk suggests that there is currently insufficient evidence to support current dietary guidelines which consolidate all dietary SFA into a single group of nutrients whose consumption should be reduced, regardless of dietary source, food matrix, and composition.